SEMANTIC FIELDS OF WINDOWS OPERATING SYSTEM TERMINOLOGY IN LINGUISTICS (British Journal of Global Ecology and Sustainable Development, 2025)
In the digital age, the integration of linguistic knowledge into technological systems has become increasingly important. Operating systems (OS), particularly Microsoft Windows, have developed specialized terminologies that reflect both their functional architectures and user interface designs. These terminologies form distinct semantic fields that help users navigate, understand, and manipulate the digital environment. The semantic field approach in linguistics provides a framework for examining how words cluster based on meaning, context, and usage. In this study, we focus on Windows OS terminology as a unique linguistic subsystem, characterized by specialized lexical units, structured categories, and conceptual metaphors. This article aims to analyze the semantic fields of Windows terminology using linguistic methods, including componential analysis, cognitive models, and corpus-based examination. The findings contribute to the broader understanding of language use in technology and offer insights into the lexicographic organization of digital environments.